Coupling isotope hydrology, geochemical tracers and emerging compounds to evaluate mixing processes and groundwater dependence of a highly anthropized coastal hydrosystem - Erostate, M.; Huneau, F.; Garel, E.; Vystavna, Y.; Santoni, S.; Pasqualini, V. (Journal of hydrology (Amsterdam), 2019)
[Display omitted] •Multi-tracers approach to identify the behavioral trends of anthropized coastal hydrosystems.•Identification of four recharge processes from a Mediterranean coastal aquifer.•Emerging compounds allow a finer temporal resolution than geochemical and isotopic tracers.•Emerging compounds with a short half life time highlight rapid infiltration of water.•Pollution study confirms the hydraulic continuity between aquifer and lagoon. Coastal aquifers can be considered as an important socio-economic and ecological component worldwide. The implementation of sustainable groundwater management is made difficult by complex hydrological behaviors due to many interactions between groundwater and fresh, brackish and salt surface water. This study proposes an original multi-tracer approach including physico-chemical parameters, trace elements, 18O, 2H, 3H of the water molecule and emerging organic compounds (EOCs) in order to improve the understanding of strongly urbanized coastal aquifers. This methodology was applied to a Mediterranean coastal aquifer in northern Corsica (France). Firstly, the isotopic data allow highlighting the complex recharge of groundwater, provided by both allochthonous rainfall from the mountain and autochthonous rainfall on the Marana-Casinca alluvial plain. Secondly, geochemical data coupled with isotopic signatures allow the identification of the different contributors and the quantification of the mixing processes into the aquifer. The residence time of groundwater were estimated with 3H. In addition, to display inertial areas with long residence time, 3H also highlights areas subject to infiltration of recent water. A better understanding of short-time hydrological processes was improved by EOCs. The study of the fate of EOCs in the environment provided a higher level of resolution than geochemical and isotopic tracers alone. Thus, the multi-tracing approach using isotopic and geochemical data, coupled with the study of the fate of EOCs, made possible to specify the conceptual model in highly anthropized hydrosystems, and particularly fast hydrological processes.